DESAIN KIT PEMBELAJARAN GERAK MENGGELINDING PADA BIDANG MIRING UNTUK SISWA SEKOLAH DASAR - Dzulfiqar Yudha Pranata; Rusydi Balfas; Mohammad Kelfiana; Zaky Vebrian; Joseph Bagas Triambada; Rima Fitria Adiati (Universitas Riau, 2023)
The experiment of rolling motion on an inclined plane can be related to everyday life and be an example of learning science while playing. This study aims to design a learning kit for rolling motion on an inclined plane for elementary school students. The research method used is research and development (R&D) which has been used to validate and develop products used in education. The result of this research is a rolling motion science learning kit design for elementary school students which consists of an inclined plane, test objects, and student worksheets. The objects used as test objects are solid cylinders, thin hollow cylinders, solid balls, hollow balls, and cubes. From the experiments, obtained variations in acceleration results ranging from 1.23 m/s2 to 3.27 m/s2. Based on experiments and simulations, the designed kit meets the theory of rolling motion and mechanics-dynamic analysis.